2018
DOI: 10.3390/su10062038
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Sustainable Competitive Advantage from the Distributor and the Supplier Networks: Evidence from the Paper-Making Industry in China

Abstract: Confronted with urgent green requirements from customers and government, firms in high pollution and high resource-consuming industries must make changes and adopt green strategies as well as knowledge-management strategies to develop and sell green products to improve sustainable competitive advantage. To study how to leverage social networks to improve sustainable competitive advantage, our article sheds light on the effects of structural holes in the distributor network as well as in the supplier network an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 85 publications
(143 reference statements)
2
9
0
Order By: Relevance
“…These results can also be concluded that the dimensions of resource-based view with resource integration, reconfiguration, and knowledge management have a significant positive effect on competitive advantage. These results are consistent with Costa et al, (2018), Holdford, (2018, Lee et al, (2016), Ma et al, (2019), Mahdi et al, (2019), Makhloufi et al, (2018), Maury, (2018), Portillo-Tarragona et al, (2018, Sudaryati & Juliasih, (2018), Torres et al, (2018), Wang et al, (2018).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results can also be concluded that the dimensions of resource-based view with resource integration, reconfiguration, and knowledge management have a significant positive effect on competitive advantage. These results are consistent with Costa et al, (2018), Holdford, (2018, Lee et al, (2016), Ma et al, (2019), Mahdi et al, (2019), Makhloufi et al, (2018), Maury, (2018), Portillo-Tarragona et al, (2018, Sudaryati & Juliasih, (2018), Torres et al, (2018), Wang et al, (2018).…”
Section: Resultssupporting
confidence: 89%
“…The knowledge management process will assist the organization in making future decisions and how to compete with competitors so that it has a significant relationship with competitive advantage (Mahdi et al, 2019). Knowledge management strategies in developing and selling products can increase competitive advantage (Wang, Han, & Liu, 2018). Knowledge management has a significant positive effect on competitive advantage (Lee, Foo, Leong, & Ooi, 2016).…”
Section: The Effect Of Knowledge Management On Competitive Advantagementioning
confidence: 99%
“…Business organizations, regardless of their size and the nature of business, have given enough attention to invest in tangible and intangible resources to gain SCP [1]. In the last decade, a burgeoning literature has discussed the factors that significantly contribute to firm performance and success such as financial capabilities [2][3][4], networking [5,6], IT capabilities [7], innovation [8][9][10], business model innovation [11,12], intellectual capital [13,14] and corporate social responsibility [4,15], etc. in developed and emerging economies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have posited that competition impedes firm's ability to maximise its potential to in terms of use of resource capabilities and market-based strategies needed to outweigh competitors and achieve competitive advantage (Aghazadeh, 2015;Doyle & Armenakyan, 2014;Ejrami, Salehi, & Ahmadian, 2016;Fatonah, 2017;Liu & Liang, 2015). Competitive advantage is critical to the success of every firm that operates in the competitive environment, and ability to achieve it is predicated upon how the firm behaves and reacts to challenging environmental situations through effective support plans and market-based strategies (Wang, Han, & Lin, 2018). The given context is however significant to how the firm deploys resources and capabilities to respond to environmental challenges and demands by making use of appropriate market-based strategy (Breznik & Lahovnik, 2016).…”
Section: Introductionmentioning
confidence: 99%